X-ray coherent mirage: Generation of phase – matched coherent point source in plasma media by propagated X-ray laser seeded beam. (30th May 2016) - Faenov, A.Ya.; Pikuz, T.A.; Magnitskiy, S.A.; Nagorskiy, N.; Tanaka, M.; Ishino, M.; Nishikino, M.; Kando, M.; Kodama, R.; Kato, Y.; Kawachi, T.
Abstract: The overview of the recent results for discovery and investigations of a very exotic phenomenon – optical mirage in the X-ray spectral range – is presented. It was found that the mirage could be created in the form of coherent virtual point source, emerging in the vicinity of the second plasma in two-stage oscillator-amplifier X-ray laser. The X-ray source-mirage, rigidly phased with the initial radiation of generator, occurs only when amplification takes place in the amplifier plasma and leads to the appearance of the interference pattern in the form of concentric rings in the spatial profile of the output X-ray laser beam. The equation describing the emergence of X-ray mirage was found, numerical solution of which shows that its formation is similar to that of the optical mirages observed at propagation of light rays through an inhomogeneously heated air. Obtained results have already demonstrated novel comprehension into the physical nature of amplification of X-ray radiation, opening additional opportunities for X-ray interferometry, holography, and other applications, which require multiple rigidly phased sources of coherent radiation.